Intelligent software methodologies, tools and techniques : 14th International Conference, SoMeT 2015, Naples, Italy, September 15-17, 2015, proceedings /: 14th International Conference, SoMeT 2015, Naples, Italy, September 15-17, 2015, proceedings. (2015) - Unknown
No abstract available